ANALISA PERBANDINGAN DINDING PENAHAN TANAH TYPE COUNTERFORT DAN CANTILEVER JALAN SIMPANG TIGA TANJUNG PALAS SEKATAK BUJI STA. 107+ STA.172 KABUPATEN MALINAU PROVINSI KALIMANTAN UTARA - NGGALA, ANTONIUS ALFONSIUS (KURVA S JURNAL MAHASISWA, 2017)
Malinau District is one of the cities in North Kalimantan province, Indonesia. This regency has an area of 18,010,50 kmÂ² which is not escape from landslide disaster, especially on highway network which is one of the most important land transportation infrastructure and is an element of regional development in North Kalimantan Province which is experiencing rapid development. High rainfall in the area of North Kalimantan, especially in Malinau District needs to be aware. Therefore, high rainfall can cause floods and landslides. One of the areas that occurred landslide disaster is access road connecting inter province that is Kaltim - Kaltara. Precisely at Simpang Tiga Tanjung Palas Sekatak Buji Malinau District of North Kalimantan Province.The purpose of writing this thesis is to be able to know how the process of handling the landslide by plotting a secure retaining wall against the rolling, shifting, and stability of the collapse of land carrying capacity at Simpang Tiga Tanjung Palas Sekatak Buji Kab.Malinau North Prov. The purpose of the preparation of this thesis is to know the calculation of the stability of retaining wall Land and Know Technical Technical design of retaining wall. Methods of data collection used in the preparation of this final task include primary data ie photo documentation, material formulas, and other calculations and secondary data include sondir, boring, and undisterd samples. Then after the data obtained then calculated using coulomb and rankine method as an analysis of the calculation of stability and carrying capacity using converse labbare.From the analysis results obtained stability factor to the style of bolsters safe, unsafe stability of the shear force, and unsatisfactory satellites against collapse on cantilever and counterfort walls.The conclusion of this final project is the result of Calculation of Land Retaining Wall Structure in the Construction of Avalanches at Simpang Tiga Tanjung Palas Sekatak Buji STA.107 + STA.172, the comparison of Kantilever type of retaining wall using Rankine method can stability value of bolsters 2,459> 2 ( safe), shear force 0.596> 2 (unsafe), stability of collapse 1.274> 3 (unsafe) and with Coulumb method obtained stability value of rolling force of 2,728 â‰¥ 2 (safe), shear force 0.696> 2 (unsafe), collapse 1.360> 3 (unsafe) While the type of counterfort with the2value of stability of rolling force of 1.864> 2 (unsafe), shear force of 1.140> 2 (unsafe), minimum land carrying capacity of 55.48, minimum carrying capacity of 5 , 53.